Systemic atherosclerosis and voiding symptom. (March 2017) - Yeniel, A. Ozgur; Ergenoglu, A. Mete; Meseri, Reci; Ari, Anıl; Sancar, Ceren; Itil, Ismail Mete
Abstract: Objective: To evaluate the effect of atherosclerosis on the storage and voiding symptoms of the bladder in women with overactive bladder (OAB). Study design: We retrospectively reviewed the charts of women with OAB who were evaluated between 2013 and 2015 in our urogynecology unit. Charts were assessed for history, examination findings, urinary diary, quality of life (QOL) questionnaires, urodynamic studies (UDSs), and four main risk factors for atherosclerosis: hypertension, diabetes mellitus, smoking, and hyperlipidemia. In a previous study, these were defined as vascular risk factors. Cases were excluded for insufficient data, diabetes mellitus with dysregulated blood glucose, or prolapse greater than 1 cm to avoid confusing bladder outlet obstruction. We included 167 eligible cases in this study. We evaluated storage and voiding symptoms such as frequency, nocturia, residual urine volume, and voiding difficulties and UDS findings such as maximum bladder capacity, first desire, strong desire, detrusor overactivity, and bladder contractility index. The vascular risk score was categorized as "no risk" if the woman did not have any of the four risk factors and "at risk" if she had any of the factors. Independent sample t -test and chi-square tests were performed for analyses. Results: Among the participants (n = 167), 71.9% had at least one vascular risk factor. Those who were at risk were facing significantly more wet-type OAB (p = 0.003) and nocturia (p = 0.023). Moreover, mean age (p = 0.008) and mean gravidity (p = 0.020) were significantly higher in the at-risk group, whereas mean total nocturia QOL questionnaire scores (p = 0.029) were significantly lower. Conclusion: Our findings suggest that aging and atherosclerosis may be associated with severe OAB and poorer QOL. Nocturia and related parameters of poor quality can be explained by impaired bladder neck perfusion. Future trials need to assess vascular and molecular changes in women with OAB.